Arthropoda yang ditemukan pada Bunga yang ditanam di sekitar Tanaman Kelapa Sawit - Zuhri, Sya’bani; Anggraini, Erise; Gurning, Friska; Pajariah, Nur; Firizki, Yuni; Sebastian Sembiring, Reginald (Seminar Nasional Lahan Suboptimal, 2024)
Zuhri, S., Anggraini, E., Gurning, F., Pajariah, N., Firizki, Y., Fesaliksa, M. A., Sembiring, R. S. (2024). Arthropod species found on flowers planted around oil palm Plants. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Indralaya  21 Oktober 2024. (pp. 76–89).  Indralaya: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Arthropods were the phylum with the largest population that dominated the animal kingdom, distributed across various regions, whether in water, on land, or hidden underground. The purpose of this research was to identify the types of visiting Arthropods and describe the morphological characteristics of the visiting Arthropods on oil palm trees, specifically in the Oil Palm Plantation of PT. R6B, Gelumbang District, Muara Enim Regency, South Sumatra. The method used was the purposive sampling method by determining observation points randomly. Each plant species had 2 observation points. Therefore, this field practice involved a total of eight observation points. The families from the Arthropod Phylum that were trapped included Aranae, Coleoptera, Diptera, Hymenoptera, Lepidoptera, Mantodea, Odonata, Orthoptera, with diversity values. Based on the results of the research, it was concluded that the family diversity at the observation site was categorized as moderate. This could be influenced by different environmental conditions and habitats.